Breast cancer screening during the adverse COVID-19 epidemiological situation - K. S. Drzhevetskaya; G. P. Korzhenkova (Исследования и практика в медицине)
Purpose of the study. To evaluate the results of breast cancer screening (BC) in the conditions of an unfavorable epidemiological situation COVID‑19 based on the analysis of the BC screening project in the Kaluga Region.Patients and methods. Screening system: creation and implementation in practice of mobile mammography complexes (MMC); training of medical personnel in the method of conducting a standardized mammographic examination (ME); quality control of ME; "Cloud" storage and software development for archiving patients; an independent review of mammograms by certified specialists; expert review of images in case of discrepancies in diagnoses; referral of patients diagnosed with BI-RADS IV and V to the regional oncological dispensary for further examination and treatment. From 04.2018 to 12.2020 patients were examined on MMC according to the BC screening protocol. We examined 47367 patients over the age of 40 years. SD 57.66 ± 8.17 years (38-93). During the COVID‑19 pandemic, imaging of breast diseases must be carried out in compliance with all safety regulations for both personnel and patients. Balancing the need to avoid delays in diagnosing BC while preventing infection requires careful attention to personal protective equipment, handling of diagnostic equipment, diagnostic facilities, and physical distancing and vigilance to maintain these measures.Results. From 07.2020 to 11.2020: a total of 10736 studies have been carried out. In the context of new coronavirus infection, we noted an increased demand among patients wishing to undergo BC screening. The flow of patients over the same period of previous years was less, which indicates the demand and justification for screening mammography and the use of MMC in an unfavorable epidemiological situation. 174 patients received category BI-RADS IV-V and were referred for a follow-up examination and required treatment at an oncological dispensary. In 39 patients (22.4 %), BC was verified, and appropriate treatment was carried out. In 135 cases, benign processes were verified.Conclusion. BC screening should not be stopped against the backdrop of the COVID‑19 epidemic since a delay in BC diagnosis later threatens to reveal more voluminous processes with a worse prognosis for treatment and rehabilitation than timely detected changes in the mammary glands in the early preclinical stages of the disease.